A method for preparing a biosensor for real-time monitoring of sialic acid

Through the biosensor modified by MnFe@NCNTs composite material, the real-time, continuous and non-invasive detection of lactic acid detection is solved, and the high sensitivity detection of lactic acid in saliva is achieved, which improves the efficiency and accuracy of clinical diagnosis.

CN115684313BActive Publication Date: 2024-12-17NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211399031.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-09
Publication Date
2024-12-17
Estimated Expiration
2042-11-09

AI Technical Summary

Technical Problem

The prior art is difficult to achieve real-time, continuous and non-invasive detection of lactic acid, and salivary lactate detection technology is in a blank period in the market, limiting the application of lactic acid in clinical diagnosis.

Method used

The biosensor modified with MnFe@NCNTs composite material was prepared by preparing the MnFe PBA material and melamine to bind to carbon nanotubes after high temperature cleavage, combined with lactate oxidase to form a mixed solution, and driply applied on a screen printing chip to achieve high sensitivity of lactic acid Test.

Benefits of technology

It realizes high sensitivity detection of lactic acid, has low detection limits and long-term stability, and can detect high sensitivity in saliva environments with complex components, improves the efficiency and accuracy of lactic acid detection, and has excellent anti-interference ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115684313B_ABST
    Figure CN115684313B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lactic acid detection, and relates to a method for preparing a biosensor for real-time detection of saliva lactic acid and its application. A high-performance MnFe@NCNTs composite material was prepared by thermal cracking of MnFe PBA material, which greatly improved the electrochemical sensing performance. The sensor printed chip prepared based on the composite material showed excellent electrocatalytic properties and electron transfer capabilities. The preparation process of the detection chip is simple and controllable, and it is easy to achieve large-scale and productized production. The biosensor based on the chip can realize the rapid identification and dynamic response of lactic acid in real saliva samples, filling the gap of real-time detection products of saliva lactic acid on the market, and greatly improving the detection efficiency of lactic acid indicators.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of clinical diagnosis and relates to a method for preparing a biosensor for real-time monitoring of sialylactic acid. Background Art

[0002] In vitro diagnosis refers to a diagnostic method that obtains clinical diagnostic information by testing samples from the human body outside the human body. It is mainly composed of diagnostic instruments and diagnostic reagents. Compared with the global market, the penetration rate of rapid testing in the entire in vitro diagnostic industry in my country is still at a low level, and the market space is broad. Lactic acid exists in a small amount in the normal human body, which represents the state of the body's circulation. It has been used as a common physiological indicator for the diagnosis of various diseases. Lactic acid is a product of glucose metabolism. When tissues are hypoxic and the body's circulatory dysfunction occurs, it can lead to glucose metabolism disorders, thereby increasing glycolysis and causing blood lactate levels to rise. Lactic acid plays a very important role in the assessment of hypoxic symptoms, the assessment of the prognosis of critically ill patients, and the monitoring and assessment of anaerobic endurance and training load of sports medicine athletes. The blood lactate concentration of healthy people is between 0.5-1mM, and that of hyperlactatemia is between 1-5mM. If the lactate concentration continues to increase and remains above 5mM, it is lactic acidosis. Therefore, lactate detection has important clinical significance.

[0003] At present, the detection of lactic acid in clinical medicine is mainly achieved through blood testing. However, conventional blood testing requires professional medical staff to operate, causes trauma and increases the risk of infection, and the detection process is time-consuming, making it difficult to achieve real-time, continuous, and non-invasive detection of lactic acid. In addition, there are still few rapid test products used for saliva lactic acid detection in my country, and the related industry is in a market gap. Therefore, the saliva diagnosis technology of lactic acid has a broad development space and application market. Summary of the invention

[0004] The present invention aims at solving the problems existing in lactic acid detection and proposes a novel method for preparing a biosensor for lactic acid detection.

[0005] In order to achieve the above object, the present invention is implemented by adopting the following technical solutions:

[0006] A method for preparing a biosensor for real-time monitoring of sialic acid, the specific steps of which are as follows:

[0007] (1) Preparation of MnFe PBA materials

[0008] The soluble manganese salt and the surfactant are dissolved in water, and a uniform dispersion is obtained after ultrasonic treatment. Then, a soluble ferricyanide solution of the same volume as the dispersion is added. After a certain period of time, a brown suspension mixture is obtained, which is aged and allowed to stand at room temperature, and then centrifuged and dried to obtain the MnFe PBA material.

[0009] (2) Preparation of MnFe@NCNTs materials

[0010] The MnFe PBA material in step (1) is mixed with melamine in a certain mass ratio, and then the mixed material is placed in a tube furnace and cracked at high temperature in an inert gas atmosphere. After the cracking is completed, a powder is obtained, and the obtained powder is transferred to a concentrated hydrochloric acid solution and heated and stirred, and then washed with a large amount of deionized water until the pH is neutral. Finally, it is filtered and vacuum dried to obtain a MnFe@NCNTs composite material.

[0011] (3) Preparation of lactate biosensor

[0012] The MnFe@NCNTs composite material was dispersed in deionized water, and then a cross-linking agent and lactate oxidase were added to form a mixed solution. A certain volume of the mixed solution was dropwise coated on the working electrode of the screen-printed chip, and the chip was placed in a refrigerator at 4°C to dry, thereby obtaining a lactate biosensor.

[0013] Preferably, the soluble manganese salt in step (1) is manganese chloride or manganese sulfate, the soluble ferrocyanide salt is potassium ferrocyanide or sodium ferrocyanide, and the molar ratio of the manganese salt to the ferrocyanide salt is 1:1, and the molar concentration of the soluble manganese salt in the dispersion and the molar concentration of the soluble ferrocyanide salt solution are the same, both of which are 5-50 mM.

[0014] Preferably, the surfactant in step (1) is any one of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate or sodium citrate, the mass ratio of the surfactant to the soluble manganese salt is (0.5-2):1, the aging time is 6-24h, the centrifugal speed is 4000-8000rpm, the drying temperature is 60°C, and the drying time is 24h.

[0015] Preferably, in step (2), the mass ratio of MnFe PBA material to melamine is 0.1-0.5, the pyrolysis temperature is 600-1000°C, the heating rate is 2-5°C / min, and the pyrolysis time is 3-6h; the inert gas is nitrogen or argon, and the gas flow rate is 5-15mL / min; the concentration of concentrated hydrochloric acid is 6-12M, the stirring time in concentrated hydrochloric acid is 4-8h, the heating and stirring temperature is 60°C, and the stirring rate is 500-800r / min; the vacuum drying time is 12h, and the temperature is 80°C.

[0016] Preferably, in step (3), the dispersion concentration of the MnFe@NCNTs composite material in deionized water is 2-5 mg / mL; the cross-linking agent is any one of chitosan, carboxymethyl chitosan, glutaraldehyde or Nafion; the volume ratio of MnFe@NCNTs dispersion: cross-linking agent: lactate oxygenase is (0.5-2):1:1; the drop coating volume of the mixed solution is 2-10 μL, and the drying time is 12-24 h.

[0017] Compared with the prior art, the advantages and positive effects of the present invention are:

[0018] 1. The present invention is based on electrochemical biosensor technology and obtains a highly stable biosensor chip through the controllable preparation of high-performance MnFe@NCNTs composite materials, which exhibits excellent electrochemical biosensor performance.

[0019] 2. The detection chip modified based on high-performance MnFe@NCNTs composite materials can achieve high-sensitivity detection of lactate, has a low detection limit, and can realize non-invasive monitoring of sialic lactate, thus improving the detection efficiency of lactate in clinical diagnosis and treatment.

[0020] 3. The lactate biosensor chip can still have high sensitivity, long-term stability, good selectivity and anti-interference ability to lactate in a complex saliva environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the scanning electron microscope image of MnFe@NCNTs.

[0022] Figure 2 This is the XRD pattern of MnFe@NCNTs.

[0023] Figure 3 This is the detection signal curve of the sensor chip for lactic acid. DETAILED DESCRIPTION

[0024] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0025] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.

[0026] Example 1

[0027] This embodiment provides a method for preparing a biosensor for real-time detection of sialylactic acid, and the steps are as follows.

[0028] (1) Preparation of MnFe PBA material: 100 mL of MnFe PBA synthesis solution A and solution B were prepared, wherein solution A was a mixture of manganese chloride and polyvinyl pyrrolidone, the concentration of manganese chloride in solution A was 5 mM, and the mass ratio of manganese chloride to polyvinyl pyrrolidone was 0.5:1. After 15 minutes of ultrasonic treatment to obtain a uniform dispersion, solution B was added, and solution B was 5 mM potassium ferrocyanide solution; the solvents of solution A and solution B were both deionized water; the mixture was aged and allowed to react at room temperature for 24 hours. After the reaction was completed, the mixed solution was centrifuged at 8000 rpm for 6 minutes and dried at 60°C for 24 hours to obtain the MnFe PBA material.

[0029] (2) Preparation of MnFe@NCNTs material: The MnFe PBA material in step (1) was mixed with melamine at a mass ratio of 0.5:1 and stirred evenly. The mixed material was then placed in a tube furnace and subjected to high-temperature pyrolysis at 1000°C under a nitrogen atmosphere. The nitrogen flow rate was 15 mL / min and the heating rate of the tube furnace was 5°C / min. After 3 hours of pyrolysis reaction, the obtained powder was collected and dispersed in 20 ml of 6M hydrochloric acid solution and heated and stirred for 4 hours at 60°C. The mixture was then washed with a large amount of deionized water until the pH was neutral. After filtration, the mixture was placed in a vacuum drying oven at 80°C for dehydration and drying for 12 hours at a vacuum degree of 0.1 MPa to obtain a MnFe@NCNTs composite material.

[0030] (3) Preparation of sialic acid biosensor:

[0031] The MnFe@NCNTs composite material in step (2) was uniformly dispersed in deionized water to prepare a 2 mg / mL dispersion, followed by the addition of chitosan and lactate oxidase, with the volume ratio of dispersion: chitosan: lactate oxidase being 0.5:1:1. 4 μL of the mixture was drop-coated on the working electrode area of ​​the screen-printed chip, and the chip was then dried in a 4°C refrigerator for 12 h to obtain a lactate biosensor.

[0032] The chip was tested for lactic acid detection performance using the square wave voltammetry technology of Shanghai Chenhua CHI660E electrochemical workstation. The voltage range was -0.6-0.6V, the increment was 5mV, the amplitude was 25mV, and the frequency was 5Hz. The three electrodes of the printed chip, namely the working electrode, the reference electrode, and the platinum electrode, were connected to the corresponding electrode wires on the electrochemical workstation using Ag / AgCl electrodes, and the electrode area was immersed in the detection system. The detection limit of lactic acid in the obtained sensor printed chip was as low as 0.1mM, the linear range could reach 0.1-1mM, the response time was 2min, and the dynamic feedback of lactic acid concentration could be achieved by sampling at intervals of 2min. After completing the standard curve test, the printed chip was stored in a PBS buffer solution at 4°C for 30 days, and its response signal was 91% of the initial signal, indicating that the lactic acid detection chip has excellent stability.

[0033] The prepared screen-printed chip was used to detect the lactic acid content (detection value) in real saliva. The detection results are shown in Table 1. The detection chip can accurately report the lactic acid content in saliva. The detection results are consistent with those of a commercial lactate analyzer (actual value), and the detection error is small, showing excellent anti-interference ability and broad practical application prospects.

[0034] Example 2

[0035] The conditions in this embodiment and subsequent embodiments that are not specifically described are consistent with those in embodiment 1. This embodiment provides a method for preparing a biosensor for real-time detection of sialylactic acid, comprising the following steps.

[0036] (1) Preparation of MnFe PBA material: 100 mL of MnFe PBA synthesis solution A and solution B were prepared, wherein solution A was a mixed solution of manganese sulfate solution and sodium dodecylbenzene sulfonate, the concentration of manganese sulfate was 50 mM, and the mass ratio of manganese sulfate solution to sodium dodecylbenzene sulfonate was 2:1. After 15 min of ultrasonic treatment, a uniform dispersion was obtained. Solution B was a 50 mM sodium ferrocyanide solution. The solvents were all deionized water. Solution B was then poured into solution A and aged at room temperature for 6 h. After the reaction was completed, the mixed solution was centrifuged at 4000 rpm for 6 min and dried at 60 °C for 24 h to obtain the MnFe PBA material.

[0037] (2) Preparation of MnFe@NCNTs material: The MnFe PBA material in step (1) was mixed with melamine at a mass ratio of 0.1:1 and stirred evenly. The mixed material was then placed in a tube furnace and subjected to high-temperature pyrolysis at 600°C under a nitrogen atmosphere. The nitrogen flow rate was 5 mL / min and the heating rate of the tube furnace was 2°C / min. After 6 hours of pyrolysis reaction, the obtained powder was collected and dispersed in 20 ml of a 12M hydrochloric acid solution and heated and stirred for 8 hours at a heating temperature of 60°C. The powder was then washed with a large amount of deionized water until the pH was neutral. After filtration, the mixture was placed in a vacuum drying oven at 80°C for dehydration and drying for 12 hours at a vacuum degree of 0.1 MPa to obtain a MnFe@NCNTs composite material.

[0038] (3) Preparation of sialic acid biosensor:

[0039] The MnFe@NCNTs composite material in step (2) was uniformly dispersed in deionized water to prepare a 5 mg / mL dispersion, followed by the addition of carboxymethyl chitosan and lactate oxidase, with the volume ratio of dispersion: carboxymethyl chitosan: lactate oxidase being 2:1:1. 4 μL of the mixture was drop-coated on the working electrode area of ​​the screen-printed chip, and the chip was then dried in a 4°C refrigerator for 24 h to obtain a lactate biosensor.

[0040] The chip was tested for lactic acid detection performance using the square wave voltammetry technology of Shanghai Chenhua CHI660E electrochemical workstation. The voltage range was -0.6-0.6V, the increment was 5mV, the amplitude was 25mV, and the frequency was 5Hz. The three electrodes of the printed chip, namely the working electrode, the reference electrode, and the platinum electrode, were connected to the corresponding electrode wires on the electrochemical workstation, and the electrode area was immersed in the detection system. The detection limit of lactic acid in the obtained sensor printed chip was as low as 0.1mM, the linear range could reach 0.1-1mM, the response time was 2min, and the dynamic feedback of lactic acid concentration could be achieved by sampling at intervals of 2min. After completing the standard curve test, the printed chip was stored in a PBS buffer solution at 4°C for 30 days, and its response signal was 93% of the initial signal, indicating that the lactic acid detection chip has excellent stability.

[0041] The prepared screen-printed chip was used to detect the lactic acid content (detection value) in real saliva. The detection results are shown in Table 1. The detection chip can accurately report the lactic acid content in saliva. The detection results are consistent with those of a commercial lactate analyzer (actual value), and the detection error is small, showing excellent anti-interference ability and broad practical application prospects.

[0042] Example 3

[0043] This embodiment provides a method for preparing a biosensor for real-time detection of sialylactic acid, comprising the following steps.

[0044] (1) Preparation of MnFe PBA material: 100 mL of MnFe PBA synthesis solution A and solution B were prepared, wherein solution A was a mixed solution of manganese chloride solution and sodium citrate, the concentration of manganese chloride was 25 mM, and the mass ratio of manganese chloride solution to sodium citrate was 1:1. After 15 min of ultrasonic treatment, a uniform dispersion was obtained. Solution B was a 25 mM sodium ferrocyanide solution. The solvents were all deionized. Solution B was then poured into solution A and aged at room temperature for 12 h. After the reaction was completed, the mixed solution was centrifuged at 6000 rpm for 6 min and dried at 60 °C for 24 h to obtain the MnFe PBA material.

[0045] (2) Preparation of MnFe@NCNTs material: The MnFe PBA material in step (1) was mixed with melamine at a mass ratio of 0.3:1 and stirred evenly. The mixed material was then placed in a tube furnace and subjected to high-temperature pyrolysis at 800°C under a nitrogen atmosphere. The argon flow rate was 10 mL / min and the heating rate of the tube furnace was 3°C / min. After 4 hours of pyrolysis reaction, the obtained powder was collected and dispersed in 20 ml of 8M hydrochloric acid solution and heated and stirred for 6 hours at a heating temperature of 60°C. Then, it was washed with a large amount of deionized water until the pH was neutral. After filtration, it was placed in a vacuum drying oven at 80°C for dehydration and drying for 12 hours at a vacuum degree of 0.1 MPa to obtain a MnFe@NCNTs composite material.

[0046] (3) Preparation of sialic acid biosensor:

[0047] The MnFe@NCNTs composite material in step (2) was uniformly dispersed in deionized water to prepare a 3 mg / mL dispersion, and then glutaraldehyde and lactate oxidase were added, with the volume ratio of dispersion: glutaraldehyde: lactate oxidase being 1:1:1. 4 μL of the mixture was drop-coated on the working electrode area of ​​the screen-printed chip, and then the chip was dried in a refrigerator at 4°C for 18 h to obtain a lactate biosensor.

[0048] The chip was tested for lactic acid detection performance using the square wave voltammetry technology of Shanghai Chenhua CHI660E electrochemical workstation. The voltage range was -0.6-0.6V, the increment was 5mV, the amplitude was 25mV, and the frequency was 5Hz. The three electrodes of the printed chip, namely the working electrode, the reference electrode, and the platinum electrode, were connected to the corresponding electrode wires on the electrochemical workstation, and the electrode area was immersed in the detection system. The detection limit of lactic acid in the obtained sensor printed chip was as low as 0.3mM, the linear range could reach 0.3-1mM, the response time was 2min, and the dynamic feedback of lactic acid concentration could be achieved through 2min interval sampling. After completing the standard curve test, the printed chip was stored in a PBS buffer solution at 4°C for 30 days, and its response signal was 92% of the initial signal, indicating that the lactic acid detection chip has excellent stability.

[0049] The prepared screen-printed chip was used to detect the lactic acid content (detection value) in real saliva. The detection results are shown in Table 1. The detection chip can accurately report the lactic acid content in saliva. The detection results are consistent with those of a commercial lactate analyzer (actual value), and the detection error is small, showing excellent anti-interference ability and broad practical application prospects.

[0050] Example 4

[0051] The difference between this embodiment and embodiment 1 is that the MnFe PBA material is not subjected to cracking treatment and is directly used as a chip modification material, and the other conditions remain unchanged. The test results show that the sensor printed chip prepared based on MnFe PBA has almost no response to lactic acid and cannot meet the actual detection requirements.

[0052] Example 5

[0053] The difference between this embodiment and embodiment 1 is that the surfactant is not pre-mixed with the soluble manganese salt solution, but is directly added to the mixed solution of the soluble manganese salt and the soluble ferrocyanide salt for stirring and reaction, and the other conditions remain unchanged. It has been verified by experiments that the sensor chip prepared based on this material has a weak response signal to lactic acid, with a detection limit of only 0.3mM and a detection range of 0.3mM-0.9mM, which cannot meet the actual detection needs.

[0054] Example 6

[0055] The difference between this embodiment and embodiment 1 is that melamine is not added, and the sensor chip based on the PB derivative is prepared, and the other conditions remain unchanged. The test results show that the detection limit of the sensor printed chip prepared based on the PB derivative for lactic acid is 0.4mM, and the detection range is 0.4mM-0.7mM, which is significantly lower than the performance of the chip in embodiment 1, which fully demonstrates that the composite structure of MnFe@NCNTs plays a key role in the detection of lactic acid.

[0056] Example 7

[0057] The difference between this embodiment and embodiment 1 is that only carbon nanotubes are used as the sensing material without compounding Prussian blue to prepare the carbon nanotube-based sensor printed chip, and the other conditions remain unchanged. The experimental verification shows that the response signal of the sensor printed chip prepared based on carbon nanotubes to lactic acid is weak, the detection limit is 0.3mM, and the detection range is 0.3mM-0.9mM, which cannot meet the actual detection needs.

[0058] From the comparison results of the above examples, it can be seen that the structure of the prepared composite sensor material plays a crucial role in the detection performance of lactic acid. Due to the low specific surface area, poor electron transmission ability and easy aggregation of Prussian blue itself, directly using it to construct a lactic acid detection chip cannot obtain ideal detection performance and cannot meet the actual detection effect. After the carbon nanotube material is introduced, the Prussian blue particles are evenly distributed on the surface of the carbon nanotubes, such as Figure 1 As shown, the dispersibility of PB particles can be improved, and at the same time, after high-temperature pyrolysis treatment, a PB porous structure is obtained, and the catalytic ability and electron transfer ability are greatly improved. In addition, the high-temperature pyrolysis method can indeed improve the catalytic ability of nanomaterials, but it has extremely high requirements for the state of the precursor. Therefore, it can be seen from Example 6 that when the Prussian blue particles that are easy to agglomerate are directly subjected to high-temperature pyrolysis, the pyrolysis products agglomerate with each other, resulting in the modified chip based on the material cannot obtain a more ideal detection performance, so in the present invention, carbon nanotubes mainly serve as carriers of Prussian blue derivatives and provide excellent electron carrying channels.

[0059] In summary, the MnFe@NCNTs composite-based detection chip prepared in the present invention has excellent electrocatalytic activity and electron transfer efficiency, and can realize the recognition and real-time monitoring of low-concentration sialylactic acid. Figure 3 As shown in the figure, its detection limit can reach 0.1mM, and the linear range is 0.1-1mM. On this basis, the prepared sensor chip can be stored in PBS buffer solution at 4°C for 30 days, and its response signal can still reach more than 90% of the initial signal. At the same time, it also shows excellent reliability and anti-interference ability in the detection of real saliva samples, and can obtain detection results within 2 minutes.

[0060] Table 1 shows the detection results of lactic acid in saliva by the sensor printed chip prepared in Examples 1-3, and the reference data comes from Mindray's fully automatic biochemical analyzer.

[0061] Table 1 Test results of lactic acid in real saliva

[0062]

[0063] From the results in Table 1, it can be seen that the lactic acid detection chip prepared in Examples 1-3 can realize the accurate detection of lactic acid in real saliva, has a low detection limit and a wide linear range, and exhibits excellent anti-interference ability and detection accuracy.

[0064] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a biosensor for real-time monitoring of sialylactic acid, characterized in that: Here are the steps: (1) Preparation of MnFe PBA materials A soluble manganese salt and a surfactant are dissolved in water to obtain a solution A, and a soluble ferricyanide solution is added after ultrasonic treatment to obtain a suspension, which is aged and allowed to stand at room temperature, and then centrifuged and dried to obtain a MnFe PBA material; (2) Preparation of MnFe@NCNTs composites The MnFe PBA material is mixed with melamine, and the mixture is placed under an inert gas atmosphere for high-temperature cracking. The powder obtained after cracking is added to a concentrated hydrochloric acid solution, heated and stirred for reaction, and then washed with deionized water until neutral; filtered and vacuum dried to obtain a MnFe@NCNTs composite material; (3) Preparation of lactate biosensor The MnFe@NCNTs composite material was dispersed in deionized water to obtain a dispersion, a cross-linking agent and lactate oxidase were added to obtain a mixed solution, the mixed solution was drop-coated on the working electrode of the screen-printed chip, and the mixture was placed in a refrigerator at 4°C to dry to obtain a lactate biosensor.

2. The method for preparing a biosensor for real-time monitoring of sialylactic acid according to claim 1, characterized in that: In step (1), the soluble manganese salt is manganese chloride or manganese sulfate, the concentration of the soluble manganese salt in solution A is 5-50 mM, the volume ratio of solution A to the soluble ferrocyanide solution is 1:1, the soluble ferrocyanide salt is potassium ferrocyanide or sodium ferrocyanide, and the molar ratio of the soluble manganese salt to the soluble ferrocyanide in the suspension is 1:

1.

3. The method for preparing a biosensor for real-time monitoring of sialylactic acid according to claim 1, characterized in that: In step (1), the surfactant is any one of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate or sodium citrate, and the mass ratio of the surfactant to the soluble manganese salt is (0.5-2):1; the aging standing time is 6-24h, the centrifugal speed is 4000-8000rpm, the drying temperature is 60°C, and the drying time is more than 24h.

4. The method for preparing a biosensor for real-time monitoring of sialylactic acid according to claim 1, characterized in that: In step (2), the mass ratio of MnFe PBA material to melamine is 0.1-0.5, the cracking temperature is 600-1000°C, the heating rate is 2-5°C / min, and the cracking time is 3-6h; the inert gas is nitrogen or argon, and the gas flow rate is 5-15mL / min; the concentration of the concentrated hydrochloric acid solution is 2-6M, the reaction time in the concentrated hydrochloric acid solution is 4-8h, the reaction temperature is 60°C, and the stirring rate is 500-800r / min; the vacuum drying time is more than 12h, and the vacuum drying temperature is 80°C.

5. The method for preparing a biosensor for real-time monitoring of sialylactic acid according to claim 1, characterized in that: In step (3), the dispersion concentration of the MnFe@NCNTs composite material in deionized water is 2-5 mg / mL; the cross-linking agent is any one of chitosan, carboxymethyl chitosan, glutaraldehyde or Nafion, the volume ratio of dispersion liquid: cross-linking agent: lactate oxidase is (0.5-2):1:1, the drop coating volume of the mixed solution is 2-10 μL, and the drying time is 12-24 h.